Impact of Chinese culture on Chinese consumers - Chen, Junsong (Henry Stewart Talks, 2009)
Understanding Chinese culture, Face culture and conspicuous consumption, Guanxi culture and gift consumption, Family culture, Dietary culture, Consumerism and Nationalism in China